La lectura comprensiva como estrategia didáctica para desarrollar el pensamiento crítico de los estudiantes de sexto año Unidad Educativa Rumiñahui, 2021 - Macay Vera, Gloria Isabel; Palacios Lino, Rosa María (Machala : Universidad Técnica de Machala, 2022)
Within the present investigation, the qualities found in the object of study are presented, which arose from the need to determine how comprehensive reading is developed as a didactic strategy in the critical thinking of sixth grade students of the Rumiñahui educational unit, 2021. We consider that our investigative work is optical because it allows us to find the research according to the knowledge to obtain access to bibliographic information and feasible because it allows us to obtain the ease of gathering empirical information through human and material resources and above all the time. to obtain professional advice. The results that we intend to extract from the study seek to show that comprehensive reading is a propitious strategy to be used in the field of language and literature, facilitating student learning, generating and making a matter of innovation, collaboration and interaction. The benefits of its use allow to increase enthusiasm, creativity and motivation, which are fundamental elements of postmodern teaching, it is linked to the formation of conscience and feelings of love, where the teacher is committed to managing learning, which is essential for a better educational mission. The paradigm of basic inquiry is channeled to the exploration of different knowledge without a specific and immediate purpose, it does not contrast with practical aspects but rather seeks comprehensive knowledge through the collection of data to establish scientific principles and laws, while research of type Descriptive takes a concept section in order to describe them, that is, it seeks to explain the relevant phenomena and characteristics of the variables involved or of the people and groups who are investigated. The approach with which the research is carried out is of a qualitative nature, because the problem is going to be observed in its real context and try to identify its nature, it focuses on phenomenology and understanding as well as being subjective with deep data and quantitative because quantitative data obtained from surveys was collected for correlation between the variables studied. The quantitative approach is one that collects and analyzes numerical or statistical data that allows the influence of the problem to be easily observed and understood. In this first chapter it is composed of the methodological framework where it allows to expose theoretical and practical methods, procedure, approach, level, instruments, techniques and research sample, together with the tabulation of data and analysis according to the results that it facilitates to answer the questions. hypothesis, with the necessary information, conclusions and recommendations were drawn. Finally, the requirement matrix is designed based on current needs. The second chapter arises from the selection of the requirement that allows the construction of the proposal, the foundation of the information, justification and the creation of the structural components. The design of the proposal is given by the guide of the objectives, such as the lack of strategies to develop a comprehensive reading and the need to strengthen the critical thinking of the students. Finally, the proposal socialized on the canva platform with a didactic guide of the relevant elements.
Dentro de la presente investigación se presentan las cualidades encontradas del objeto de estudio el cual surgió de la necesidad de determinar cómo se desarrolla la lectura comprensiva como estrategia didáctica en el pensamiento crítico de los estudiantes de sexto grado de la unidad educativa Rumiñahui, 2021. Consideramos que nuestro trabajo investigativo es óptico porque nos permiten encontrar la investigación acorde a los conocimientos para obtener acceso de información bibliográfica y factible debido a que permite obtener la facilidad de recopilación de información empírica por medio de los recursos humanos, materiales y sobre todo el tiempo de obtener asesoramiento profesional. Los resultados que pretendemos extraer del estudio procuran manifestar que la lectura comprensiva es una estrategia propicia para emplear en el campo de la lengua y la literatura, facilitando el aprendizaje de los estudiantes, generar y hacer un asunto de innovación, colaboración e interacción. Los beneficios de su uso permiten aumentar el entusiasmo, la creatividad y la motivación, que son elementos fundamentales de la enseñanza posmoderna, está ligado a la formación de la conciencia y los sentimientos de amor, donde el docente está comprometido en el manejo de aprendizaje, que es esencial para una mejor misión educativa. El paradigma de indagación básica está encauzada a la exploración de diferentes conocimientos sin una finalidad específica e inmediata, no contrasta con aspectos prácticos sino que busca un conocimiento integral mediante la recolección de datos para establecer así principios y leyes científicas, mientras que la investigación de tipo descriptiva toma una sección de concepto con la finalidad de describirlas, es decir, busca explicar los fenómenos y características relevantes de las variables involucradas o de personas y grupos a quienes se investigan. El enfoque con el que se trabaja la investigación es de carácter cualitativo, porque se va a observar el problema en su contexto real y tratar de identificar su naturaleza, se centra en la fenomenología y comprensión además de ser subjetivo con datos profundos y el cuantitativo porque se recopiló datos cuantitativos obtenidos de encuestas para correlación entre las variables estudiadas. El enfoque cuantitativo es aquel que recopila y analiza datos numéricos o estadísticos que permiten observar y comprender la influencia del problema fácilmente. En este primer capítulo se compone del marco metodológico donde permite exponer métodos teóricos y prácticos, procedimiento, enfoque, nivel, instrumentos, técnicas y muestra de investigación, junto a la tabulación de datos y análisis de acuerdo a los resultados que facilita dar respuesta a las hipótesis, con la información necesaria se procedió a plantear conclusiones y recomendaciones. Finalmente se diseña la matriz de requerimiento en base a las necesidades de la actualidad. El segundo capítulo surge a partir de la selección de requerimiento que permite la construcción de la propuesta, la fundamentación de la información, justificación y la creación de los componentes estructurales. El diseño de la propuesta se da por la guía de los objetivos, como la falta de estrategias para desarrollar una lectura comprensiva y la necesidad de fortalecer el pensamiento crítico de los educandos. Finalmente la propuesta socializada en la plataforma canva con una guía didácticas de los elementos relevantes.
Keywords: ENSEÑANZA-APRENDIZAJE; APRENDIZAJE SIGNIFICATIVO; PLATAFORMA DIGITAL; CANVA –PICTOTRADUCTOR